EXPERIMENTAL INVESTIGATION OF REINFORCED CONCRETE FLEXURAL BEAMS STRENGTHENED OR REPAIRED WITH CFRP (Journal of Engineering, 2009)
Fiber reinforced polymers are typically comprised of high strength fibers (e.g. carbon and glass) impregnated with an epoxy (often termed the matrix). Experimental investigations of the behavior of reinforced concrete beams, strengthened or repaired by CFRP for flexural case have been presented in this paper. The experimental program consisted of 14 test beams. The study took into account strengthened and repaired cases in using CFRP; therefore, similar beams were used once for strengthening and once for repairing to make a comparison between them. All beams had been tested in a simply supported span and subjected to two-point loading while the main variable is the quantity, distribution and location of CFRP. The beams included additional anchorage at the ends of the main CFRP sheet reinforcement to prevent end separation of CFRP sheet. The results of experiments show that the use of CFRP as external strengthening has significant enhancement on ultimate load, crack pattern and deflection. It is observed that the use of external CFRP in strengthening or repairing beams could enhance the ultimate load capacity up to 160% over the capacity of the identical reference (untreated) beam.